2019
DOI: 10.1108/bfj-03-2019-0195
|View full text |Cite
|
Sign up to set email alerts
|

Trust factors for organic foods: consumer buying behavior

Abstract: Purpose The purpose of this paper is to assess the relationship between trust factors and buying behavior among consumers in the organic food market in Taiwan. Design/methodology/approach The researchers developed a questionnaire using latent variables including the trust factors, utilitarian attitudes, hedonic attitudes, buying behavior and demographic information of consumers of organic foods. Confirmatory factor analysis and the structural equation modeling were conducted using LISREL 8.80 for Windows. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 63 publications
1
67
1
2
Order By: Relevance
“…Besides, our study refutes the research by Aitken et al (2020), Teng and Wang (2015) and Lee et al (2020) that showed a direct and positive relationship between certification and the intention to purchase organic food. Hamzaoui-Essoussi et al (2013), Liang et al (2016) and Teng and Wang (2015) founded that the presence of certification on organic food could increase the consumers' trust in that kind of food.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Besides, our study refutes the research by Aitken et al (2020), Teng and Wang (2015) and Lee et al (2020) that showed a direct and positive relationship between certification and the intention to purchase organic food. Hamzaoui-Essoussi et al (2013), Liang et al (2016) and Teng and Wang (2015) founded that the presence of certification on organic food could increase the consumers' trust in that kind of food.…”
Section: Discussioncontrasting
confidence: 56%
“…Although it did not analyze the label's presence on organic food, the research could indicate the relevance of certification to the consumers' purchase intention. Lee et al (2020) also demonstrated that organic labels impact consumer buying behavior and encourage more consumers to purchase organic food. Therefore, we present hypothesis:…”
Section: Bfj 1236mentioning
confidence: 98%
See 1 more Smart Citation
“…Researchers presented various consumers' motives for buying organic food such as ecological sustainability [29], healthy lifestyles [13]. Extant literature focused on understanding various reasons to consume organic food [9,30,31], and the motives behind a consumer's behavior [32].…”
Section: Introductionmentioning
confidence: 99%
“…The production of organic foods is environmentally friendly; it does not utilize antibiotics, growth hormones, pesticides, chemical fertilizers or growth regulators. Organic foods are often regarded as more friendly to environmental agriculture and, ultimately, as healthier than conventional, non-organic foods [1].…”
Section: Organic Farming Productsmentioning
confidence: 99%